TRENDS IN THE EVOLUTION OF WATER REQUIREMENTS, THEIR USE AND ENSURE BY THE FACILITIES AND HYDROTECHNIC STRUCTURES IN SIRET RIVER BASIN - DAN DĂSCĂLIŢA (Aerul şi Apa: Componente ale Mediului, 2013)
Romania fits into areas with relatively poor water resources, compared to other regions of the world, ranked 29 in Europe. Siret River Basin level, water resources are in the same situation still occupies an important place in the total resources of the country. Economic and social development requires the provision of additional water requirements, but wich should be used sensibly. Representing the Water resource taken directly from natural sources of surface and ground water, requirement ensures water supply used in various destinations such as population and industrial and agricultural businesses. The water resource is not evenly distributed in time and space. Also, and its use is done unevenly, with maximum requirement periods, medium or low. There are periods when the water requisit are not covered by unarranged direct sources even though technological processes are equipped with internal water circulation systems or connected external to water networks. In order to ensure water requirements in any situation and in any case with deficite hydroclimatic or with maximum requirements of perspective, on the watercourse are realized hydrotechnics works, according complex planning schemes a hydrographical basins. Thus, the water courses have been furnished with accumulations, derivatives and water intakes which now provides full water requirements. In the Siret River Basin, hydrotechnics works were made in correlation with social and economic development, wich in the decade 1980-1990 recorded the largest water requirements. Reducing economic activities correlated to reducing water loss from networks distribution but and with modernization of the technological processes, the last two decades have led to significant reductions in water requirements. Under these conditions some hydrotechnic arrangements with main water alimentation role, have changed initial functions or are in the process of redevelopment to become profitable and maintain aquatic and adjacent terrestrial ecosystems. In this paper we present some aspects regarding the trends of evolution water requirements and Facilities and hydrotechnic structures with role by water alimentation of the users from the Siret River Basin.